Development and validation of clinical profiles of patients hospitalized due to behavioral and psychological symptoms of dementia. Issue 1 (December 2016) - Ortoleva Bucher, Claudia; Dubuc, Nicole; von Gunten, Armin; Trottier, Lise; Morin, Diane
Abstract Background Patients hospitalized on acute psychogeriatric wards are a heterogeneous population. Cluster analysis is a useful statistical method for partitioning a sample of patients into well separated groups of patients who present common characteristics. Several patient profile studies exist, but they are not adapted to acutely hospitalized psychogeriatric patients with cognitive impairment. The present study aims to partition patients hospitalized due to behavioral and psychological symptoms of dementia into profiles based on a global evaluation of mental health using cluster analysis. Methods Using nine of the 13 items from the Health of the Nation Outcome Scales for elderly people (HoNOS65+), data were collected from a sample of 542 inpatients with dementia who were hospitalized between 2011 and 2014 in acute psychogeriatric wards of a Swiss university hospital. An optimal clustering solution was generated to represent various profiles, by using a mixed approach combining hierarchical and non-hierarchical (k-means) cluster analyses associated with a split-sample cross-validation. The quality of the clustering solution was evaluated based on a cross-validation, on a k-means method with 100 random initial seeds, on validation indexes, and on clinical interpretation. Results The final solution consisted of four clinically distinct and homogeneous profiles labeled (1)BPSD-affective, (2)BPSD-functional, (3)BPSD-somatic and (4)BPSD-psychotic according to their predominant clinical features. The four profiles differed in cognitive status, length of hospital stay, and legal admission status. Conclusion In the present study, clustering methods allowed us to identify four profiles with distinctive characteristics. This clustering solution may be developed into a classification system that may allow clinicians to differentiate patient needs in order to promptly identify tailored interventions and promote better allocation of available resources.